The rabha tribe of North-East India, Bengal and Bangladesh - Basumatary, Phukan (New Delhi, 2010)
This book is a short monograph of the Rabhas. It incorporates chiefly two major genres i.e. cultural and linguistic features. The analysis has been done based on the field-data collected from primary and secondary sources.
Keywords: Rabha (Indic people)-Social life and customs